Protective effects of connexins in atheromatous plaques in patients of carotid artery stenosis. Issue 2 (13th October 2016) - Nakase, Taizen; Ishikawa, Tatsuya; Miyata, Hajime
Abstract: Fragility of atheromatous plaque in the internal carotid artery can be a risk of brain infarction. The activation of macrophages by oxidative stress and the vulnerability of vascular endothelial cells have been reported to participate in the fragility of atheromatous plaque. Therefore, from the view point of prevention of brain infarction, we investigated the pathological factors which may influence the stabilization of atheromatous plaque. Patients undertaking carotid endoarterectomy (CEA) were continuously screened. Then, 21 samples were obtained from the atheromatous plaques of CEA patients. The expression of connexin (Cx) which composes a gap junction, an intercellular communication organ, was immunohistochemicaly observed. The expression of CD36, an oxidized low‐density lipoprotein receptor, was assessed as a marker of oxidative stress. As a result, asymptomatic plaques which were assumed the stable plaques expressed Cx43 along with CD36 expression. In contrast, in the symptomatic plaques, the expression of Cx43 was few and there was almost no coexpression with CD36. The distribution of Cx37 expression was not different between asymptomatic and symptomatic plaques. The expressions of CD36, Cx37 and Cx43 showed no relation to the previous treatment with statins. In conclusion, Cx43 might contribute to the stabilization of atheromatous plaque which is affected by oxidative stress.